Implementation of Digital-preneurship Fitur in Supporting the Quality of Human Resources - Benny Kusuma, Yoseph; Prosto Skenoma, Yudha; Desma Rahadhini, Marjam; Putri Macca Aliandheart, Azwa (KnE Social Sciences, 2024)
The COVID-19 pandemic resulted in the increasing need for digitalization as well as a need to improve the quality of human resources to implement digitalization. This study aimed to find out how digital-preneurship supports the quality of human resources on Etawa goat farms in Blitar Regency. This research was exploratory in nature and used a descriptive qualitative method that compared observations and literature studies. The subjects were 7 informants who were taken by purposive sampling and saw their credibility. Data was collected through interviews. The results of this study indicated that human resources at Etawa goat farms in Blitar Regency have digital-preneurship knowledge and competence in caring for and raising goats, but knowledge about digitalization was still at the communication stage and involved using social media on smartphones. Other results also showed that the existing human resources need training to package dairy products and market them on social media, so this research suggested establishing cooperation and partnerships with the government and stakeholders to improve human resource capabilities in using social media in the marketing and selling Etawa goat farm products in Blitar Regency. Keywords: digitalization, human resources, Covid-19